An Incident at the Era of the Reformation; from a Contemporary Manuscript (Proceedings of the Society of Antiquaries of Scotland, 1876)
This article discusses a manuscript dealing with the legal action of the Bishop of Dunblane, William Chisholm, against Jane, Lady Fleming, for the repayment of a loan of £250 from 1559-60. The author begins by describing the lives of the two people involved. He then goes on to present a transcription of the manuscript’s text.